A Low-Profile Dual-Polarized Antenna with High Isolation and High Front-to-Back Ratio for 5G Base Stations - Ciydem, M. (Applied Computational Electromagnetics Society Journal (ACES), 2021)
A dual-polarized, broadband, slot-coupled patch antenna design is presented for sub-6 GHz 5G base stations. Proposed antenna is made up of two suspended stacked patches above feedline layer and is excited by crossed elliptic-H slots for ±45º slant, linear dual polarized operation. Prototyped antenna has an impedance bandwidth of 22.1% (3.14 - 3.92 GHz) for |S11|, |S22| < −15 dB and port isolation |S21| is also obtained to be < −28 dB in this band. Antenna exhibits directional radiation patterns with half power beamwidths of 57º - 65º and 60º - 64º in elevation and azimuth planes, respectively with varying gain of 8.6 - 9.1 dBi. Proposed antenna is also low profile (11.1 mm) with high front-toback ratio (> 27 dB) without reflector. Design details, numerical studies, and measurement results are presented.